CRDT-based knowledge synchronisation in an Internet of Robotics Things ecosystem for Ambient Assisted Living - Galeas, José; Tudela, Alberto; Pons, Óscar; Bandera, Juan Pedro; Bandera, Antonio; Bustos, Pablo (Computer vision and image understanding, 2025)
Integrating IoT and assistive robots in the design of Ambient Assisted Living (AAL) frameworks has proven to be a useful solution for monitoring and assisting elderly people at home. As a way to manage the information captured and assess the person’s condition, respond to emergencies, promote physical or cognitive exercises, etc., these systems can also integrate a Virtual Caregiver (VC). Given the diversity of technologies deployed in such an AAL framework, deciding how to manage knowledge appropriately can be complex. This paper proposes to organise the AAL framework as a distributed system, i.e., as a collection of autonomous software agents that provide users with a single coherent response. In this distributed system, agents are deployed locally and handle replicas of the knowledge model. The problem of merging these replicas into a consistent representation, therefore arises.The δ-CRDT (Conflict-free Replicated Data Type) synchronisation mechanism is employed to ensure the eventual consistency with low communication overhead. To manage the dynamics of the AAL ecosystem, the δ-CRDT is combined with the publish/subscribe interaction protocol. In this way, the performance of the IoT, the robot and the VC, through the functionalities that depend on them, is efficiently adapted to changes in the context. To demonstrate the validity of the proposal, two use cases have been designed in which a collaborative response from the system is required. The first one deals with a possible fall of the user at home, while the second one deals with the problem of helping the person move small objects around the flat. The measured values of latency or consistency in the data show that the proposal works satisfactorily. [Display omitted] •States an IoRT framework for AAL as a distributed system.•Guarantees the consistency of a distributed knowledge model using δ-CRDT.•Integrates δ-CRDT with the publish/subscribe interaction model.•Evaluation in real-world experiments shows that the approach is a practical solution.